2006
DOI: 10.1002/cphc.200600477
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on Optical Rotation: A Case Study of Methyloxirane in Water

Abstract: A long-standing challenge in molecular stereochemistry is to assess the contributions of the solvent surrounding chiral organic molecules. The observed specific rotation angles and optical rotatory dispersion (ORD) spectra are strongly influenced by solvent-solute interactions. For example, (S)-methyloxirane has a positive optical rotation (OR) in water and a negative OR in benzene.[1] The vapor phase and condensed phase optical rotations of chiral molecules are also known to differ in large and nonintuitive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(157 citation statements)
references
References 26 publications
13
141
1
2
Order By: Relevance
“…A promising, if computationally expensive, alternative is to combine molecular dynamics (MD) simulation with quantum chemical sampling of the solute and explicit solvent molecules. [40][41][42] In an attempt to keep the computational cost of the MD-based approach at a minimum, Kundrat and Autschbach 43,44 have shown that a simple point charge representation of the solvent molecules (water) may be used to simulate explicit solvent effects in the quantum chemical sampling. As noted by these authors, the MD-based scheme may also be used as an alternative to Boltzmann averaging to account for conformational effects.…”
Section: Introductionmentioning
confidence: 99%
“…A promising, if computationally expensive, alternative is to combine molecular dynamics (MD) simulation with quantum chemical sampling of the solute and explicit solvent molecules. [40][41][42] In an attempt to keep the computational cost of the MD-based approach at a minimum, Kundrat and Autschbach 43,44 have shown that a simple point charge representation of the solvent molecules (water) may be used to simulate explicit solvent effects in the quantum chemical sampling. As noted by these authors, the MD-based scheme may also be used as an alternative to Boltzmann averaging to account for conformational effects.…”
Section: Introductionmentioning
confidence: 99%
“…[5] It would be of great interest to follow the solvation process by sequentially solvating PO with more water molecules to conclusively establish the trend.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent theoretical simulations showed that, interestingly, the optical rotation response in an aqueous environment is dominated by that of the binary PO···water complex rather than of the PO monomer itself. [5] In addition, a tentative conclusion that the water molecules bind preferentially to PO in the anti rather than in the syn position was drawn, by comparing the simulations with the experimental results. [4,5] Here, anti or syn refers to the side of PO that is opposite to or the same as the methyl group, respectively.…”
Section: Zheng Su and Yunjie Xu*mentioning
confidence: 99%
See 1 more Smart Citation
“…b) Qualitative Situation für Methyloxiran (nach den Daten aus Lit. [9,11] oder eine ¾nderung des Aggregationsverhaltens des chiralen Moleküls.…”
unclassified